From Legacy Systems to Digital Solutions: Change Management in IT Transformations - Zangana, Hewa Majeed; Mohammed, Harman Salih; Husain, Mamo Muhamad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The transition from legacy systems to modern digital solutions is a pivotal aspect of IT transformations that demands meticulous planning and execution. This study examines the role of change management in IT transformations by exploring key factors such as stakeholder engagement, risk mitigation, and alignment of technology with organizational goals. A mixed-methods research approach was employed, integrating both qualitative and quantitative methodologies. The qualitative aspect involved expert interviews and case studies from multiple industries, while the quantitative approach utilized statistical regression analysis on survey responses from IT professionals. Key performance indicators (KPIs) such as project success rates, adoption levels, and cybersecurity resilience were analyzed to assess the impact of change management strategies. The study identifies a strong correlation between agile methodologies and increased organizational adaptability, emphasizing the importance of iterative development, continuous feedback, and cross-functional collaboration. Findings highlight that integrating change management frameworks with IT project delivery enhances efficiency and reduces resistance to digital transformation. This research provides a comprehensive framework for organizations aiming to optimize their IT transition processes and maximize the benefits of digital transformation.